The Influence of Social Media Use on Students’ Morals at Madrasah Aliyah Negeri 3 Tabalong, South Kalimantan - Riska Reysa; Ria Susanti; Khairul Washfiah (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
The rapid advancement of digital technology has significantly transformed the way students communicate, access information, and interact within society. Among these technological developments, social media has become an inseparable part of adolescents' daily lives, offering both educational opportunities and moral challenges. This study aims to examine the influence of social media use on students' moral behavior at Madrasah Aliyah Negeri (MAN) 3 Tabalong, South Kalimantan. A quantitative research approach was employed using a survey method. The study involved a population of 152 students, from which 35 respondents were selected through purposive sampling. Data were collected through questionnaires, interviews, observations, and documentation. The collected data were analyzed using descriptive statistics, validity and reliability tests, simple linear regression, product-moment correlation, t-test, and coefficient of determination analysis. The findings reveal that the calculated t-value (3.430) exceeded the critical t-table value (1.692), indicating a statistically significant relationship between social media use and students' moral behavior. The regression analysis produced the equation Y = 33.390 + 0.479X, demonstrating a positive linear relationship. Furthermore, the coefficient of determination indicates that social media use contributes 21.8% to students' moral development, while the remaining 78.2% is influenced by other factors outside the scope of this study. These findings highlight that although social media significantly influences students' morals, teachers, parents, and schools remain essential in fostering responsible digital behavior and strengthening students' moral character.